Perkembangan Jumlah Penduduk Dan Umr Terhadap Jumlah Pengangguran Di Provinsi Sumatera Utara Tahun 2007-2019 - Putri Sari M J Silaban (Jayapangus Press, 2020)
Population and UMR are factors contributing to the pace of development of unemployment. The purpose of this research is to determine the influence of population and UMR on the amount of unemployment in North Sumatera province. The method of analysis used is multiple regression analysis with the help of software EViews 9. The secondary data used is data time series 2007-2019 period taken from North Sumatra in numbers. An independent variable consists of population and UMR while the dependencies variable is unemployment amount. The results showed that the total population and UMR variables have a significant effect on the total unemployment in the province of North Sumatra.